Study of Pap smear and other feasible tests among self reported symptomatic married women in reproductive age group (15-49 yrs) regarding reproductive tract infections in a rural community of Maharashtra - Chavan, Smita S.; Giri, Purushottam A.; Singh, Vijaykumar S.; Sankaranarayan, Shantha (International Journal of Research in Medical Sciences, 2017)
Background: Reproductive tract infections (RTIs) represent a major public health problem in developing countries. Integrating RTIs/STIs management and early detection of cervical dysplasia in broader reproductive health services can improve women’s health. The objectives of the study were 1. To study the association of socio-demographic & reproductive factors among self-reported symptomatic women for reproductive tract infections. 2. To carry out clinical examination & feasible tests like PH, gram staining, VDRL for reproductive tract infections. 3. To study Pap smear among study subjects. Methods: A cross sectional study community based study was carried out in villages under ‘Parol’ Primary Health Centre of Thane district, Maharashtra, India. A total of 415 married women in reproductive age group were interviewed and examined. Pre-structured, pre-designed questionnaire was used. Clinical examination & feasible laboratory tests were done. Results were analyzed with the help of Microsoft Excel & SPSS 15. Results: A total of 415 women were interviewed, of them 263(63.4%) had one or more symptoms of reproductive tract infections. On examination, 69(35%) had cervicitis and 30(15.2%) pelvic inflammatory disease, 39(19.8%) bacterial vaginosis and candidiasis in 61(31%). Cervical erosion was present in 147(74.6%) women. On Pap smear, 20(10.2%) women had ASCUS (Atypical squamous cells of undetermined significance). Only 2(1%) women found HIV positive. No woman was found VDRL reactive. Conclusion: Routine RTI/STI screening and periodic surveys to detect the infection patterns which will helps to control HIV infections in the community is needed in the remote tribal area as the current study shows high prevalence of reproductive tract infection.